ENSO impacts on Atlantic watersheds of South America - Isla, Federico Ignacio; Toldo Junior, Elirio Ernestino (Quaternary and Environmental Geosciences, 2013)
Interannual changes in precipitation cause significant effects on the Pacific watersheds of South America. Large rivers flowing to the Atlantic Ocean as the Paraná and Uruguay are also influenced by ENSO-triggered floods causing significant impacts on the economies of Argentina, Brazil and Uruguay. At the same time, the floodplains of small rivers are also sensitive to strong ENSOs. Floods occur approximately simultaneously in subtropical watersheds of Brazil and high-latitude watersheds of North Patagonia. ENSO-triggered floods were recorded during the years 1941-42, 1982-83 and 1997-98. Several floods impacted along the Itajaí River affecting the higher (Blumenau city) and lower estuary (Itajaí city). The Guaiba River, at the headlands of Lagoa dos Patos, has repeatedly flooded Porto Alegre. At the Río de la Plata basin, significant increases in the discharges were assigned to the Paraná and the Uruguay rivers. The small basin of the Quequén Grande River without extended floodplains is subject to periodic failure of its margins. The Colorado River, the northern limit of Patagonia, is allochthonous and its watershed was artificial and progressively modified; the ENSO event of 1983 caused an increase in its salinity due to the sudden reactivation of the Desaguadero-Curacó system.